Morbidities among older people in Bangladesh: evidence from an ageing survey - Kalam, I. M. Shafiqul; Khan, Hafiz T. A. (BRAC University, 2010)
In recent decades, the population structure in many countries has been reshaping due to combined effect of falling fertility and increased life expectancy. Because of demographic interaction, a trend of increasing proportion for aged 60 years or more has emerged which cause new concerns to academics, researchers and policy makers. Although ageing is relatively a new demographic phenomenon in Bangladesh, demographers however believe that it will have profound impact on the economy, politics and society as a whole. As more people live longer, retirement, pensions and other admissible social benefits tend to extend over longer periods of time. This makes it necessary for social security systems to change substantially in order to remain effective in particular for keeping the elderly in good shape. This paper attempts to explore the types of illness among older people in Bangladesh using data collected from a national survey. It also describes the factors associated with health situation of the elderly in Bangladesh.